2005
DOI: 10.1016/j.jtcvs.2004.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Visceral pleural invasion is an invasive and aggressive indicator of non-small cell lung cancer

Abstract: Visceral pleural invasion is a significant poor-prognostic factor, regardless of N status. Our analyses indicated that visceral pleural invasion is an independent indicator of non-small cell lung cancer invasiveness and aggressiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
140
5
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(162 citation statements)
references
References 25 publications
14
140
5
3
Order By: Relevance
“…The overall incidence of VPI in NSCLC has been documented as 11.5-26.8% (4,15). Considering that VPI occurs only when tumor-pleura contact is direct, the exact incidence of the peripheral tumors has not been reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall incidence of VPI in NSCLC has been documented as 11.5-26.8% (4,15). Considering that VPI occurs only when tumor-pleura contact is direct, the exact incidence of the peripheral tumors has not been reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by Maeyashiki et al (19), the maximum dimension of consolidation in part-solid GGNs was a significant predictor of lymph node positive status and poor prognosis. Shimizu and colleagues (4) suggested that tumors with VPI had usually moderate or worse differentiation and had a higher scar grade (tumors had fibroblastic tissue with amount of collagen fibers). In our case series, larger consolidation area was associated with higher rate of VPI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, mediastinal lymph node involvement and the number of metastatic lymph nodes are important negative prognostic factor in surgically resected stage IIIA NSCLC [2]. Additionally, visceral pleural invasion was observed more frequently in biologically aggressive NSCLCs, and by multivariate analysis, this invasion proved to be a significant independent predictor of grim prognosis, with or without lymph node involvement [3]. Therefore, in most NSCLC cases, the therapeutic strategy is based on the tumor stage and on the performance status of the patient at diagnosis.…”
Section: Introductionmentioning
confidence: 95%
“…We further analyzed the characteristic features of tumor cells among patients who underwent anatomic resection, in order to identify its effect on disease-free and overall survival rates. Previous studies had reported that several pathological factors were related to survival rate; these factors include visceral pleural invasion, [19][20][21][22] vascular invasion, [23] perineural invasion, [24][25][26] histologic grade, [27] and nuclear atypia. [28] Our multivariate analysis indicated that only perineural invasion had a significant effect on disease-free and overall survival rates among N2 NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%